The Caribbean Single Market and Economy (CSME) : the international environment and options for CARICOM and the OECS countries - Lewis, Vaughan A. (Jamaica Ian Randle Publishers, 2006)
Examines the changing conditions under which the CSME came into existence, and under which its implementation is taking place. Suggests that the quickening pace of integration arrangements in the North Atlantic economy as a whole, requires for CARICOM and the OECS, not simply a change of pace of trade liberalization, but a change of focus. Suggests also that CARICOM needs to focus on hastening the establishment of its own Regional Integration Fund and that the OECS governments assume a special responsibility for proposing the new approach to the EPA negotiations.
Published for the UWI-CARICOM Project
Keywords: Foreign Policy; Foreign Relation; Foreign Trade; Caribbean Single Market and Economy; CSME